Commotion in the ocean - Andreae, Giles- 1966-; Wojtowycz, David, ill. (Waukesha, Wis. : Little Tiger Press, 1998)
A collection of peoms about the many creatures living beneath the sea, including crac, dolphin and angel fish.
NP
Keywords: Marine animals -- Poetry; English poetry